Occult follicular lymphoma in a swollen regional lymph node of gastric schwannoma - Shuichi Fukuda; Taichi Koyama; Tomoko Wakasa; Hitoshi Hanamoto; Tomoyuki Tsujimoto; Atsushi Gakuhara; Hideo Tomihara; Katsuya Ohta; Kotaro Kitani; Kazuhiko Hashimoto; Hajime Ishikawa; Jin-ichi Hida; et al. (Surgical Case Reports)
Abstract Background Regional lymphadenopathy is more commonly noted in gastric schwannomas than in other gastric submucosal tumors. Most of the swollen lymph nodes associated with gastric schwannomas are non-metastatic lymphadenopathy. Case presentation A 69-year-old Japanese woman was referred to our hospital with a chief complaint of abdominal discomfort. Contrast-enhanced computed tomography (CT) of the abdomen revealed an extraluminal tumor with heterogeneous enhancement at the middle stomach on the lesser curve, accompanied with one swollen lymph node approximately 10 mm in size and several small lymph nodes in the perigastric region. These lymph nodes were flat; therefore, we considered them to be non-metastatic. The main tumor was removed via wedge resection. Soft and slightly swollen lymph nodes, which were compatible with the lymph nodes noted in the preoperative CT, were found near the main tumor in the fatty tissue at the lesser curvature of the stomach. An excisional biopsy of the largest lymph node was performed for the diagnosis. Based on pathological findings, a diagnosis of gastric schwannoma and follicular lymphoma (FL) was confirmed. The patient is doing well without recurrence of either the gastric schwannoma or FL 28 months postsurgery. Conclusions The present report detailed an extremely rare case of FL coincidentally discovered in the swollen regional lymph node of gastric schwannoma.